2020
DOI: 10.1002/cssc.202000175
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalytic Hydrogenation of Levulinic Acid to γ‐Valerolactone with Formic Acid as Internal Hydrogen Source

Abstract: As one of the most promising biomass‐based platform molecules, γ‐valerolactone (GVL) can be synthesized from a variety of lignocellulosic feedstocks through different hydrogen supply pathways. Among these transformation routes, the hydrogenation of levulinic acid (LA) to GVL by using formic acid (FA) as the internal hydrogen source is regarded as a critical path for the sustainable development of renewable energy systems. Although a large number of studies on the synthesis of GVL have been reported, the FA/LA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 122 publications
0
38
0
Order By: Relevance
“…The use of FA as H‐donor has recently drawn significant research interest [13c] . It is produced as a byproduct during downstream processing of biomass, and therefore the use of FA can eliminate the requirement of external H‐donors in future biorefinery setups [39] .…”
Section: Furfuryl Alcohol (Fol)mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of FA as H‐donor has recently drawn significant research interest [13c] . It is produced as a byproduct during downstream processing of biomass, and therefore the use of FA can eliminate the requirement of external H‐donors in future biorefinery setups [39] .…”
Section: Furfuryl Alcohol (Fol)mentioning
confidence: 99%
“…Formic acid (FA) is an important biomass‐derived chemical that can be produced in equimolar amount during the synthesis of LA via hydrolysis of 5‐HMF [13c] . Several research groups have demonstrated that FA can be used as H‐donor for GVL production from LA.…”
Section: Transfer Hydrogenation Of Levulinic Acid (La) To Gamma‐valermentioning
confidence: 99%
“…In this regard, 4-hydroxyvaleric acid, which is the intermediate of interest for the MPV intermolecular hydrogenation mechanism (path B, Scheme 2), was not detected in the reaction mixture. In principle, LA is firstly adsorbed on the surface of the catalyst and subsequently esterified with methanol (MeOH) to methyl levulinate, benefiting from the Lewis acidity of the catalyst [22]. To investigate the mechanism of LA adsorption on the catalysts, in situ FT-IR analysis was performed.…”
Section: La To Gvl Catalytic Testsmentioning
confidence: 99%
“…However, Ruppert et al have demonstrated that formic acid can be irreversibly adsorbed on the Ru/C catalyst, hampering the LA conversion to GVL [21]. Furthermore, agglomeration and metal leaching generally occur, which could greatly affect catalyst stability, thus significantly hampering its effective use [22]. Alternatively, it is possible to use alcohol as an H 2 source, and perform a hydrogen transfer, which is known as the Meerwein-Ponndorf-Verley (MPV) reaction, which is catalyzed by Lewis acid sites, such as those of metal oxides or zeolites [23].…”
Section: Introductionmentioning
confidence: 99%
“…The products of the dehydrogenation reaction of FA are It is obvious that the dehydration reaction reduces the selectivity to the desired hydrogen. Furthermore, carbon monoxide can poison metallic centers due to its strong adsorption ability on metals that may decrease their activity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%